1414 Insights Into Neonatal Oral Feeding Pathology Through Rna Sequencing of Salivary Samples. (October 2012) - Maron, JL; Bodi, KL; Johnson, KL; Bianchi, DW
Abstract : Background and Aims: To improve our understanding of newborn feeding pathophysiology at the molecular level, our laboratory studies transcripts in neonatal saliva. Previously, we used whole transcriptome microarrays. Here, we tested the hypothesis that sequencing of RNA would provide additional and more specific information. Methods: RNA was extracted and prepared for sequencing from salivary samples (10 µL) collected from two term infants matched for post-conceptual age, gender and ethnicity who could and could not orally feed, respectively. Paired-end 100 x 100 base pair sequencing was performed on the Illumina HiSeq 2000. Sequence data were aligned against human reference genome GRCH37/hg19. Cuffdiff analysis identified differentially expressed genes, promoters, and splicing variants between subjects. Ingenuity Pathway Analysis was performed on statistically significantly differentially expressed genes. Results: There were 405 genes, 3 splicing variants, and 2 promoters that were statistically significantly different between case and control. We detected abnormal thyroid function, impaired myelination, and delayed ossification of the mandible in the poor oral feeder (10 –5 < p<10 –2 ). Genes involved in neurodevelopment, hyperphagia, and adipocyte development were differentially expressed between subjects (10 –3 < p<10 –2 ). Conclusions: Targeted comparative RNA sequencing analyses identify global, and patient specific, aberrations in developmental pathways directly related to oral feeding pathology. Our study demonstrates the feasibility of neonatal salivary sequencing for identifying key regulatory genes and pathways that are differentially expressed and regulated between successful and unsuccessful oral feeders, and suggests that this approach will lead to new insights into neonatal pathophysiology.